SMART ABDOMEN MODEL AS CLINICAL LEARNING MEDIA IN IMPROVING MIDWIFERY STUDENT COMPETENCE IN POSTPARTUM CARE - Herlyssa; Elly Dwi Wahyuni; Jujun Dwi Astuti; Sri Rahayu (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
This study aims to determine the effectiveness of the